STUDENTS' KNOWLEDGE OF SUBJECTS IN THE CREDIT-MODULE SYSTEM FORMULATING EVALUATION CRITERIA (American Journal of Business Management, Economics and Banking, 2022)
This article provides information on assessment, control questions in the credit module system.